Uso de sedativos em idosos: preditor de queda e fratura de fêmur entre idosos atendidos em um ambulatório de geriatria. - Nelson Machado do Carmo Júnior (2022)
The use of benzodiazepine sedatives and benzodiazepine-related sedatives (zdrugs) in geriatrics is discussed in the literature because it involves more risks than benefits in this population, including the occurrence of falls and fractures. The present study aims to investigate the use of sedatives among older people attended at a private geriatrics outpatient clinic in Belo Horizonte (MG), as well as its association with falls and femoral fractures. This is a longitudinal study, in which the prevalence of benzodiazepines and z-drugs use among older people was described and their association with the incidence of falls and fractures was evaluated using logistic regression. A total of 7,821 elderly people were included in the study, most of them female (72.5%), mean age of 77.5 years and an average Clinical Functional Vulnerability Index (IVCF-20) of 16.5 points. The prevalence of use of sedatives in general was 6.19%, with 4.48% of benzodiazepines and 1.98% of z-drugs. The most used sedative drugs were clonazepam (29.0%), zolpidem (28.6%) and alprazolam (23.4%). Fall was reported for 182 patients (2.33%), with a higher incidence among sedative users (4.34; p=0.002; OR=1.94 adjusted for gender, age and IVCF-20) and benzodiazepines (5.14%; p<0.001; OR=2.28) than among non-users (2.19%). Femoral fractures were identified in 33 patients (0.42%), being more frequent among users of sedatives (1.03%; p=0.032; OR=2.57) and benzodiazepines (1.43%; p= 0.003; OR=3.45) than among non-users (0.38%). It is concluded that the incidence of falls and femoral fractures in the elderly is associated with the use of sedative drugs, especially benzodiazepines.